2004
DOI: 10.1089/pho.2004.22.527
|View full text |Cite
|
Sign up to set email alerts
|

A Morphologicalin VitroStudy of the Effects of Nd:YAG Laser on Irradiated Cervical Dentin

Abstract: We concluded that the use of the Nd:YAG laser was a very effective measure for obliterating dentinal tubule openings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
7

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
6
0
7
Order By: Relevance
“…In the laser group, our results were similar to those of Lan et al 29,30 and De Magalhães et al, 28 who assessed the effi cacy of Nd:YAG laser on the root surface and dentinal tubules. However, there were slight differences in the radiation parameters and methodologies used by these studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the laser group, our results were similar to those of Lan et al 29,30 and De Magalhães et al, 28 who assessed the effi cacy of Nd:YAG laser on the root surface and dentinal tubules. However, there were slight differences in the radiation parameters and methodologies used by these studies.…”
Section: Discussionsupporting
confidence: 89%
“…[3][4][5]28 Several treatment alternatives have been proposed to manage this condition, which basically act by sealing dentinal tubules. In this study, we assessed the sealing ability of Nd:YAG laser and a new resin on exposed dentinal tubules by SEM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The Nd:YAG laser application reported by some investigators exhibited, under SEM analysis, surface alterations such as charring, crater formation, and cement meltdown. 38,[46][47][48][49][50][51][52][53][54] Studies with Nd:YAG laser using different parameters 47,48 have shown that mean power settings ranging between 1.25-3.00 W promote a root surface change leading to fusion and resolidification of the cement mineral portion alongside crack and fissure formation. Thomas et al 46 reported that the Nd:YAG laser denatures root surface proteins, and they suggest that the complement of the conventional mechanical treatment of the root surface would be important on the reduction of these irregularities aiming for a more biocompatible root surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of success in routine treatments, in the mid-1980s, the use of a laser to decrease the level of DH was proposed. In most of the cases, lasers such as Nd:YAG, CO 2 , and Er:YAG were used and a relative success was described [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%